Tri Mandala: Kearifan Lokal Bali dalam Pembagian Zonasi dan Ruang pada Bangunan Pura di Kabupaten Sidoarjo - Wasudewa Bhattacarya; Edi Dwi Riyanto (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This study examines the Tri Mandala as Balinese local wisdom in the division of zoning and space in temple buildings in Sidoarjo Regency. Tri Mandala is a regional division concept that divides the temple building into three parts, there are Nista Mandala, Madya Mandala, and Utama Mandala. The purpose of this study is to explain the form of Tri Mandala as Balinese local wisdom in the division of zoning and space in temple buildings in Sidoarjo Regency. To achieve the research objectives, this research used observational interview and in-depth interview techniques. This research data analysis method uses interpretative descriptive analysis techniques. The result of this research is that the Tri Mandala concept explicitly determines the zoning and space division of the temple building. Although located outside the area of ​​Bali, the temple in Sidoarjo Regency still maintains the Tri Mandala concept with some adjustments that are adjusted to local needs and conditions without reducing the meaning of the Tri Mandala concept.